Consultative congresses of the rolling stock and traction engineers: activity оf L. M. Levi - Berdnychenko, Yu. A.; Kyrychenko, H. I. (History of science and technology, 2018)
An up-to-date task of modern historical science is a comprehensive study of prominent personalities having made a significant contribution to the formation and development of world science. The article is devoted to the analysis and systematized generalization of a set of scientific facts that objectively characterize various aspects of the activities of outstanding railroad engineer Liudwih Mavrykiiovych Levi in the consultative congresses of the rolling stock department engineers. In the history of science and technology, L.M Levi is known as a prominent locomotive designer, who almost all his life devoted to the development and improvement of locomotives. While preparing this paper chronological, typological, comparative methods of historical knowledge, as well as the classification and systematization of historical sources and bibliographic material which allowed to systematize and critically evaluate the used sources have been applied. Using these methods we highlighted the main point in the current state of studying the topic and the results of other researchers, characterized previous works on this problem and clearly singled out issues not having been sufficiently studied yet. The sources analysis made it possible to give an objective appraisal of the contribution made by L. Levi during his participation in the consultative congress of rolling stock and traction engineers. His role in solving the problems on implementing the “Compound system” on steam engines has been shown. Further development and improvement of which became possible only with the introduction of steam. There was an increase in traction force of locomotives and rolling stock of freight trains. It was found that thanks to the personal contribution of L. M. Levi to the unification of parts for different types of rolling stock, water supply and signaling devices, there was a reduction in the operating costs of railways. This was achieved thanks to the mass production of spare parts, as well as individual locomotives and wagons with the help of specially adapted workshops. The study of transport science through the biography of a scientist, is an integral part of a complex of diverse knowledge, involves the use of a systematic approach as a methodological means of scientific knowledge. It opens up the possibility to combine the structure and content of empirical tools from one point of view with theoretical ideas and requires the consideration of controversial views on the inheritance of national railway scientists and L.M. Levi in particular.